2013
DOI: 10.1155/2013/132827
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Analysis of the Kinetics of Thermal Inactivation of Enzyme

Abstract: A theoretical model of Illeova et al. (2003) thermal inactivation of urease is discussed. Analytical expressions pertaining to the molar concentrations of the native and denatured enzyme are obtained in terms of second-order reaction rate constant. Simple and closed form of theoretical expression pertains to the temperature are also derived. In this paper, homotopy analysis method (HAM) is used to obtain approximate solutions for a nonlinear ordinary differential equation. The obtained approximate result in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…This unifying simplification is of interest for researchers focusing attention on the phenomenological process rather than the mechanistic description of the kinetics of heat induced enzyme deactivation. However, the multi-temperature evaluations revealed that an adequate kinetic model has to incorporate at least three reaction steps [16]. Although, the three-step mechanism model of inactivation of the enzyme has been developed by Illeova et al [16], there is no provision of either exact or approximate analytical solutions (except by Ananthi et al [16]) for the predictions of model concentrations of the native enzyme, denature enzyme and temperature for thermal inactivation of urease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This unifying simplification is of interest for researchers focusing attention on the phenomenological process rather than the mechanistic description of the kinetics of heat induced enzyme deactivation. However, the multi-temperature evaluations revealed that an adequate kinetic model has to incorporate at least three reaction steps [16]. Although, the three-step mechanism model of inactivation of the enzyme has been developed by Illeova et al [16], there is no provision of either exact or approximate analytical solutions (except by Ananthi et al [16]) for the predictions of model concentrations of the native enzyme, denature enzyme and temperature for thermal inactivation of urease.…”
Section: Introductionmentioning
confidence: 99%
“…However, the multi-temperature evaluations revealed that an adequate kinetic model has to incorporate at least three reaction steps [16]. Although, the three-step mechanism model of inactivation of the enzyme has been developed by Illeova et al [16], there is no provision of either exact or approximate analytical solutions (except by Ananthi et al [16]) for the predictions of model concentrations of the native enzyme, denature enzyme and temperature for thermal inactivation of urease. Ananthi et al [16] applied the homotopy analysis method to develop approximate analytical solutions for the analysis of kinetic and thermal inactivation of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation